Prospects for Strengthening the Geopolitical Contours of the Union State - I. F. Kefelia; V. G. Kogut; G. N. Nuryshev (Евразийская интеграция: экономика, право, политика, 2025)
This work is devoted to the analysis of the results of 25 years of the formation of the Union State.   Aim and tasks. To define the geopolitical dimension of the Union State as an integration project of Russia and the Republic of Belarus. To study the main results of the Union State’s activities over 25 years of its formation. To analyze the main directions of development of the single geopolitical space of the Union State. To assess the geopolitical determinants of the integration association of Russia and the Republic of Belarus.   Methods. Research of publications and other materials on the topic under study based on the geopolitical paradigm, methods of analysis and synthesis, induction and deduction, qualitative content analysis.   Results. The study revealed the nature of the geopolitical subjectivity of the Union State in the new geopolitical configuration in Europe.   Conclusions. The Union State is acquiring the image of a full-fledged constructor of the post-Soviet geopolitical space after its erosion. It has become an indicator of the understanding by Russian and Belarusian society of the level of their geopolitical self-identification and awareness of the geopolitical future of their countries in the new geopolitical and geoeconomic architecture of the modern world.